Anther culture in rice: from an experimental model to breeding practice - Usenbekov, B.; Mukhambetzhanov, S.; Kurbangaliyeva, T.; Amirova, A.; Sartbayeva, I.; Kirshibaev, E.; Gabdullina, Ye.; Yerezhepov, D.; Yerezhepov, A. (Fundamental and Experimental Biology, 2026)
The anther culture method has become an effective tool in modern rice breeding, enabling a significant reduction in the breeding cycle through the rapid production of haploid and doubled haploid plants. Extensive global experience, particularly in major rice-producing countries such as China, Japan, and India, confirms the importance of androgenesis technology for developing new high-yielding and high-quality rice varieties. The efficiency of this method depends on multiple interacting factors, the most critical being genotype. Studies have shown that the japonica subspecies of rice is markedly more responsive and suitable for anther culture, whereas the indica subspecies is typically exhibits low callus induction and regeneration capacity. To overcome these limitations, inter-subspecific hybridization and optimization of culture protocols are commonly employed. This approach has also been successfully implemented in Kazakhstan, where several new rice lines and varieties have been developed. In particular, the cultivar Fatima demonstrates increased productivity ( 5.1 t/ha) and valuable agronomic traits and has already been released for cultivation in the country’s major rice-growing regions. Moreover, anther culture has enabled Kazakhstani breeders to obtain doubled haploid lines surpassing their parental forms in several agronomic characteristics, such as the glutinous variety Violetta. In conclusion, anther culture in rice holds considerable potential for accelerating the development of homozygous lines and novel genotypes. The integration of this approach with molecular tools such as marker-assisted selection (MAS) and CRISPR/Cas9 genome editing offers new opportunities for targeted gene combination and for expediting the development of improved rice varieties with desired traits.